On the fractional domain generalization of memristive parametric oscillators. Issue 1 (1st January 2019) - Banchuin, Rawid
Abstract: In this research, we generalize a family of electronic parametric oscillators in the fractional domain by using a state of the art circuit element namely fractional memristor. Such family of parametric oscillators is the memristor based Wien family which is an extension of the normal Wien family. Noted that such normal Wien family is one family of the simplest second-order nonparametric oscillators. We derive the equations of the range of oscillating frequency, sustained oscillating frequency, sustained oscillating condition and the output voltage by using our mathematical model of the fractional memristor as the basis. With the obtained results and numerical simulations, the effects of the fractional memristor to the generalized parametric oscillators have been studied where the validation has been performed based on the SPICE HP memristor model. We have found that those oscillators with the fractional memristor of order greater than unity are more preferable.